INOVASI KOMPOSISI BUMBU HITAM BERBAHAN DASAR KACANG GUDE, JAMUR SHIITAKE, KLUWEK DAN BLONDO DITINJAU DARI UJI ORGANOLEPTIK. - Kristian Agung Nugraha; Hari Minantyo; Devina Irtanto; Ivana Grasielda; Trifosa Jesslyn Gracia (JURNAL ILMIAH EDUNOMIKA, 2026)
Food innovation based on local ingredients is growing along with increasing consumer demand for more natural, functional, and sustainable foods. The diversity of Indonesian spices makes Indonesia one of the countries with a rich and complex culinary tradition. The development of ready-to-use seasonings based on local ingredients presents a strategic opportunity to increase the added value of local commodities and strengthen national food security. Indonesia has a variety of local food ingredients that have the potential to be developed into innovative seasonings, including pigeon peas, shiitake mushrooms, kluwek, and blondo.  This research can contribute to the expansion of the variety of Indonesian ready-to-use seasonings that have a strong culinary identity and can be marketed widely, including through UMKM platforms, modern retail, and exports of traditional food products. Based on these opportunities, this research is designed to develop black spices made from gude nuts, shiitake mushrooms, kluwek, and blondo as modern local spice innovations. This research aims to formulate the best composition for making black spices based on local ingredients, evaluate sensory characteristics through organoleptic testing, and produce scientific information that can strengthen the local spice industry. Based on the results of the research discussion, it can be concluded that the differences in blondo composition in samples A1 to A4 have different effects on the product's sensory characteristics. The color of all samples is dominated by black derived from the use of kluwek, which has been shown to have strong and stable pigmentation capabilities despite variations in the composition of other ingredients. In the color category, there was a significant difference in the level of preference, with sample A1 being the most preferred and sample A2 showing a significant difference compared to the other samples.   Keywords: Blondo, Bumbu Hitam, Inovasi Bumbu